Realising the Right to Primary Education for Refugee and Asylum-Seeking Children in Cameroon: Appraising the Legal Framework, Compliance and Challenges - Agbor, Doreen N.; Agbor, Avitus A. (Comparative and International Law Journal of Southern Africa, 2024)
In international and regional human rights law, the right to education is arguably one of the most important rights since it is a social, economic, and cultural right and has a direct bearing on the enjoyment of civil, political, social, economic and cultural rights. For vulnerable groups, emphasis has always been placed on the need to respect, protect, fulfil, and promote the right to education, given the crucial role it plays in promoting peace, stability, and socio-economic and personal development. Two critical issues arise when looking at the children of refugees and asylum seekers: firstly, their vulnerability as involuntary migrants who have fled their home countries and settled in another country. Secondly, as children, they remain vulnerable to different forms of exploitation. Against this background, and in view of the huge number of refugees and asylum seekers in Cameroon, this study examines some of the measures taken by Cameroon to give effect to her international obligations as a State Party to numerous human rights instruments (both international and regional) recognising the right to compulsory and free primary education for children. To do this, the study commences with an assessment of the international human rights framework and identifies the various obligations created by those instruments that serve as benchmarks for evaluating whether Cameroon has fulfilled her international and regional obligations. The study analyses the challenges encountered in this regard and offers some insights on what could be done to surmount those challenges.